Deconstructing Life Cycle Expenditure - Aguiar, Mark; Hurst, Erik (Journal of Political Economy, 2013)
We revisit two well-known facts regarding life cycle expenditures: the “hump”-shaped profile of nondurable expenditures and the increase in cross-household consumption inequality. We document that the behavior of total nondurables masks surprising heterogeneity in the life cycle profile of individual consumption subcomponents. We provide evidence that the categories driving life cycle consumption either are inputs into market work or are amenable to home production. Using a quantitative model, we document that the disaggregated life cycle consumption profiles imply a level of uninsurable permanent income risk that is substantially lower than that implied by a model using a composite consumption good.